Structures and diffusion motions of K and Ca in biomass ash slags from molecular dynamics simulations. (15th October 2021) - Ma, Charlie; Skoglund, Nils; Carlborg, Markus; Broström, Markus
Highlights: Study of structure and diffusion in relation to viscosity of CaO–K2 O–SiO2 slags. Local structures of Ca and K cations linked to changes in composition and viscosity. Clustering of K ions facilitated diffusion via percolation channels. Ca and K cations showed hopping diffusion motions through the silicate network. The presence of Ca cations reduced the diffusivity of K cations. Abstract: The ash slag formations that can occur in combustion and gasification of solid fuels often consist of silicate melts that can cause operational problems, e.g., bed agglomeration or slag build-up. This study aims to better understand the underlying molecular structures and motions that bring about viscosity variations in biomass ash slags that are rich in Ca and K. Aspects of slag structure, diffusivity, and cation motion in the molten CaO–K2 O–SiO2 system were acquired from molecular dynamics simulations. These results are discussed in relation to viscosity values found in literature. Among the structural characteristics of the silicate network, the simulations showed that the local structures of both Ca and K were affected by composition, with stronger integration of Ca within the silicate network than K. The formation of larger ring structures due to network depolymerisation occurred with increasing diffusivity and lower viscosity, but small rings prevailed due to clusters of Si and O atoms that formed cohesive structures. Both Ca and K showed hopping motions as they diffused through the network, especially in high viscosity compositions. These cations exhibited preferential migration to positions previously occupied by the same species, as a means of moving around the network-forming Si and O atoms that diffused slower. The diffusivity of K ions was facilitated by transport in percolation channels. The presence of slower-diffusing Ca ions occupied positions that could otherwise have contributed to K diffusivity. This work contributes towards understanding of ash slags in thermochemical processes by exploring network modifier mobility in silicate slags. .